Evaluation of the use and quality of water in the east axis section of the São Francisco river integration project - Caldas, Hidaiane Fayga Matias; Marques, Érika Alves Tavares; Sobral, Maria do Carmo (Seven Editora, 2023)
The present work aims to evaluate the water quality along the eastern axis of the São Francisco River integration project. For this, the statistical resource of Principal Components Analysis was used. DOI: https://doi.org/10.56238/methofocusinterv1-050